Chronic Disease Prevalence and Medicare Advantage Market Penetration - Steven W. Howard; Stephanie Lazarus Bernell; Faizan M. Casim; Jennifer Wilmott; Lindsey Pearson; Caitlin M. Byler; Zidong Zhang (SAGE Publishing, 2015)
By March 2015, 30% of all Medicare beneficiaries were enrolled in Medicare Advantage (MA) plans. Research to date has not explored the impacts of MA market penetration on individual or population health outcomes. The primary objective of this study is to examine the relationships between MA market penetration and the beneficiary's portfolio of cardiometabolic diagnoses. This study uses 2004 to 2008 Medical Expenditure Panel Survey (MEPS) Household Component data to construct an aggregate index that captures multiple diagnoses in one outcome measure (Chronic Disease Severity Index [CDSI]). The MEPS data for 8089 Medicare beneficiaries are merged with MA market penetration data from Centers for Medicare and Medicaid Services (CMS). Ordinary least squares regressions are run with SAS 9.3 to model the effects of MA market penetration on CDSI. The results suggest that each percentage increase in MA market penetration is associated with a greater than 2-point decline in CDSI (lower burden of cardiometabolic chronic disease). Spill-over effects may be driving improvements in the cardiometabolic health of beneficiary populations in counties with elevated levels of MA market penetration.